KEKERASAN DALAM RUMAH TANGGA (KDRT) DALAM PERSPEKTIF PSIKOLOGI DAN PENANGANANNYA MENURUT ISLAM - Aries Dirgayunita; Robiatul Adawiyah (IMTIYAZ: Jurnal Ilmu Keislaman, 2018)
Human being is a unique creature. This uniqueness can be source of sustainability, peace, and happiness if managed properly. In fact, the are a lot of gaps of ideal realm and its reality as reflected in abundance of domestic violence whether it is physically, verbally, sexually, or ecomically. This kind of violence continuously happens despite PKDRT (Penghapusan Kekerasan dalam Rumah Tangga) Law. This is because the implementation of the Law has not yet been widespreading. This article aims at exploring the causes of domestic violence, the forms, the implications, and how to avoid and handle it from individual sphere until the wider sphere like society and government from psychological and Islamic perspective